The functioning of academic employees in a dynamic South African higher education environment - ChaaCha, Thapelo D.; Oosthuysen, Elrie (Frontiers in Education, 2023)
The higher education sector is experiencing changes in the profile of employees and stakeholders. Current employees are expected to function effectively and efficiently in institutions to achieve individual and organisational goals. The functioning aspect of the capability approach presents the opportunity to investigate how academic employees function in the current work environment. The study aimed to investigate the functioning of academic employees in the current work environment. Understanding how academic employees function in their current work environment provides the opportunity to develop relevant talent management practices to motivate, retain, support, develop, and lead academic employees. A qualitative research approach and a critical realism perspective was utilised to explore social relations in the sample environment. Purposive sampling was employed to identify appropriate participants for the study. Nine online semi-structured interviews were used to collect data from the participants. The findings of the study show that academic employees function effectively when they experience support and relationships at work as well as when autonomy and technology are available among various aspects of work. Talent management strategies require proactive reviewing to meet academic employees’ needs to enhance performance. Human resource practitioners and leaders in the institution have the responsibility to explore the functioning of academics in their environment to understand how they can enhance their performance and develop and retain these employees to meet institutional goals. The study adds some insights to the current literature related to the functioning of academic employees using the capability approach. The institution can develop new mechanisms to enhance the performance of these employees in a dynamic environment through talent management practices.